Development of the recipe and technology of semi-finished mock cutlets of functional purpose - A. B. Tkhaishaova; Z. N. Khatko; N. A. Loban (Новые технологии, 2023)
Increase in animal protein resources is of great importance on a global scale. Proteins of animal origin provide the human body with basic macroand micronutrients and support normal human life and activities. Poultry meat occupies a significant proportion in the state program of production and sale of animal proteins. From year to year, the growth and consumption of poultry meat (30...35 %) is constantly increasing. Mechanically deboned poultry meat is characterized by less technological potential and is in need of increase its functional and technological properties in the formation of food systems with specified properties.The article shows the possibility of expanding the assortment of meat chopped semi-finished products (cutlets) of functional purpose using a compositional mixture in a recipe that helps to increase biological and nutritional value.The purpose of the research is to develop the recipe and technology of mechanically deboned poultry meat semi-finished products (cutlets) of functional purpose using non-traditional raw materials, namely compositional mixture (CM).The qualitative and quantitative composition of the compositional mixture for cutlets of functional purpose from mechanically deboned poultry meat has been substantiated and selected.The influence of the dosage of the compositional mixture consisting of a solid Adygh cheese«Mate» (powder), oatmeal and garlic powder, on the consumer properties of mechanically deboned poultry meat has been investigated. The quality indicators (organoleptic and physico-chemical ones) cutlets of functional purposes have been investigated.The recipe and technology of functional cutlets has been developed where wheat bread is replaced completely (100%) with a compositional mixture and coating with oatmeal flour. This technology has shown the best quality indicators.